Analysis Of The Influence Of Digital Marketing Technology And Facilities On Visitor Satisfaction Of Tamora Watterland Swimming Pool - Tambunan, Sontina Griche (Bahasa Indonesia, 2023)
This study aims to partially and simultaneously analyze between Digital Marketing and facilities on the satisfaction of visitors to the Tamora Waterland swimming pool. Respondents used as many as 100 visitors with data collection through questionnaires that were distributed directly. This research method is quantitative and processed using Service Solution or abbreviated (SPSS) version 2 0 and Microsoft Excel. The result of the study is the use of digital marketing technology as a promotional medium is very influential on the satisfaction of swimming pool visitors. Likewise, the facilities provided by the pool manager also affect visitor satisfaction. Simultaneously, both variables affect the satisfaction of swimming pool visitors.